2019
DOI: 10.21873/invivo.11638
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Comparison of Infectious Endocarditis and Non-infectious Endocarditis: A Review of 814 Autoptic Cases

Abstract: Aim: We examined evidence on infective and noninfective endocarditis obtained from a database of 50,403 clinical autopsies performed at an Italian general hospital between January 1983 and December 2006. Materials and Methods: Out of 814 endocarditis cases, 409 were of infective endocarditis (IE) and 405 non-infective (NIE). The median age at the time of death was 78 years for those with IE and 83 for those with NIE. Data were collected on gender, clinical history, comorbidities, kind of affected valve (nonpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 18 publications
2
40
0
4
Order By: Relevance
“…Endocarditis is an inflammation of the heart valve and endocardium, which is characterized by the formation of vegetation, and it can be bacterial or NBTE. Pre-existing valve damage was the most common predisposing factor, as the most common valvular lesions found in males were cardiac valvular dystrophic sclerocalcifications, whereas post-rheumatic valve lesions were found in females [3]. The incidence and prevalence of NBTE are unclear since the diagnosis of NBTE is most commonly made at autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocarditis is an inflammation of the heart valve and endocardium, which is characterized by the formation of vegetation, and it can be bacterial or NBTE. Pre-existing valve damage was the most common predisposing factor, as the most common valvular lesions found in males were cardiac valvular dystrophic sclerocalcifications, whereas post-rheumatic valve lesions were found in females [3]. The incidence and prevalence of NBTE are unclear since the diagnosis of NBTE is most commonly made at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas another study found 405 cases out of a total of 10,874 autopsies, representing 3.7% of cases. Malignant neoplasms were found in 59%, and thrombosis was found in 38% of NBTE cases [3]. NBTE is characterized by thrombi deposition on normal heart valves without the presence of a bloodstream infection, and it typically occurs in the setting of chronic debilitating diseases such as cancer and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Endocarditis is defined as inflammation of the endocardium that typically affects the heart valves and is characterized by the formation of vegetations 9 . It is uncommon for the TV to be involved in noninfective endocarditis compared to the left‐sided valves, 9 therefore, the term TV endocarditis mainly refers to infective endocarditis (IE). Although right‐sided infective endocarditis (RSIE) only makes up 5% to 10% of IE cases, TV infective endocarditis (TVIE) makes up to 90% of RSIE cases 10 …”
Section: Disease Of the Tvmentioning
confidence: 99%
“…It is unclear what is driving this disparity, or the clinical significance given that long term outcomes showed no gender disparity. Marantic endocarditis (ME) is difficult to differentiate from infective endocarditis (IE) [1]. We demonstrate an atypical case of ME presenting as an independently-mobile mass and severe MR. A 57-year-old man presented with a right parietal stroke secondary to mitral valve(MV) endocarditis.…”
mentioning
confidence: 93%